Konten Sejarah Pemberontakan Shimabara dalam The Musical Touken Ranbu:“Shizuka no Umi no Paraíso” - Siti Nurhalisa; Yessy Harun (Universitas Al Azhar Indonesia, 2023)
This research discusses the historical context of the Shimabara Rebellion in The Musical Touken Ranbu: “Shizuka no Umi no Paraíso”. The historical story of the Shimabara Rebellion attracted an entertainment company called Nelke Planning to include the story of this rebellion in its musical, The Musical Touken Ranbu with the title The Musical Touken Ranbu: “Shizuka no Umi no Paraíso”. This study aims to analyze the historical context of the musical and find out the differences and similarities between the original history and the musical. The method used in this research is descriptive analysis. This research was obtained through a literature study from history books, journals, articles, previous research and The Musical Touken Ranbu itself. The results of this study indicate that the factors causing the Shimabara Rebellion were the high tax burden for the ikkoku ichijo (one castle per province) policy and discrimination against Christians in Japan. This policy made the people impatient, and in the end, they carried out a rebellion to get justice. Therefore, this rebellion became the greatest rebellion that ever happened in the Edo period. Many modifications are made for entertainment purposes but do not forget the historical elements.Keywords - Shimabara Rebellion, The Historical Story, The Musical Touken Ranbu.